Cooperation of Kazakhstan and India in the Field of Science This (Journal of Oriental Studies, 2018)
This article examines the ways of development of science of the two countries in the context ofmutually beneficial cooperation between Kazakhstan and India in the field of science. The main areasof science development and their beneficial use for the opposite side are analyzed. Two countries Indiaand Kazakhstan, which are at different levels of development, find common ground and profitable useof available resources.